Defining the Dynamic Regulation of O-GlcNAc Proteome in the Mouse Cortex---the O-GlcNAcylation of Synaptic and Trafficking Proteins Related to Neurodegenerative Diseases - Huynh, Van N; Wang, Sheng; Ouyang, Xiaosen; Wani, Willayat Y; Johnson, Michelle S; Chacko, Balu K; Jegga, Anil G; Qian, Wei-Jun; Chatham, John C; Darley-Usmar, Victor M; Zhang, Jianhua (Frontiers in Aging, 2021)
O-linked conjugation of ß-N-acetyl-glucosamine (O-GlcNAc) to serine and threonine residues is a post-translational modification process that senses nutrient availability and cellular stress and regulates diverse biological processes. Pharmacological increase of protein O-GlcNAcylation by Thiamet G (TG) that inhibits O-GlcNAcase (OGA) has been shown to decrease tau phosphorylation and neurotoxicity, and proposed as a therapy in Alzheimer’s disease (AD). However, acute TG exposure impairs learning and memory, and protein O-GlcNAcylation is increased in the aging rat brain and in Parkinson’s disease (PD) brains. To define the cortical O-GlcNAc proteome that responds to TG, we injected young adult mice with either saline or TG and performed mass spectrometry for detection of O-GlcNAcylated peptides in the cortex. This approach identified 506 unique peptides corresponding to 278 proteins that are O-GlcNAcylated. Of the 506 unique peptides, 92 peptides are elevated by >1.5 fold in O-GlcNAcylation levels in response to TG. Using pathway analyses, TG-dependent enrichment of O-GlcNAcylated synaptic proteins, trafficking, Notch/Wnt signaling, HDAC signaling, and circadian clock proteins were detected. Significant changes in the O-GlcNAcylation of DNAJC6/AUXI, and PICALM, proteins that are risk factors for PD and AD respectively, were identified. We compared our study with 2 key prior studies using mouse cerebral tissue and human AD brains. Among those we identified to be increased by TG, 15 are also identified to be increased in human AD brains compared to control, including those involved in cytoskeleton, autophagy, chromatin organization and mitochondrial dysfunction. These studies provide insights regarding neurodegenerative diseases therapeutic targets.